BIO-CHEMICAL EVALUATION OF MANGO ( TION OF MANGO (MANGIFERA I NDICA L.) CV. KESAR AT DIFFERENT LOCATIONS IN SAURASHTRA REGION (GUJ REGION (GUJARAT) - V. M., CHOVATIYA; SANANDIA, S. T.; AGHERA, S. R. (The Bioscan, 2016)
The present investigation entitled “Bio-chemical evaluation of mango (MangiferaindicaL.) cv. Kesar at Saurashtra region” was carried out at Department of Horticulture and Food Testing Laboratory, College of Agriculture, Junagadh Agricultural University, Junagadh during the year 2013-14. Nine different locations from Saurashtra region were selected for this experiment viz., Una, Mendarda, Bheshan, Junagadh (Sakkarbaug), Talala, Vanthali, Dhari, Aadityana and Ghogha. The harvested sample fruits from different locations were cleaned, ripened at room temperature in paper boxes, than used for further bio-chemical evaluation. The experiment was conducted in Completely Randomized Design.In the experiment,comparatively highest results were found formost of biochemical parameters in fever of treatment L5 (Talala)viz.,total sugar content (117.78 mg/g), non-reducing sugar content(87.33 mg/g), lowest acidity (0.21 %), lowest ascorbic acid content (42.46 mg/100g pulp) Whereas in treatment L1 (Una) higher reducing sugar content (26.85 mg/g) was found. The myth has been proven to be real from this scientific study. From the conducted experiment over nine different locations, it can be concluded that the Talala is more congenial for mango cv. Kesar or it can be truly say that mango orchards located at/near Talala region produces better quality fruits as compared to others.